Impact of early thiopurines on surgery in 2770 children and young people diagnosed with inflammatory bowel disease: a national population‐based study. Issue 8 (13th August 2015) - Chhaya, V.; Pollok, R. C. G.; Cecil, E.; Subramanian, V.; Curcin, V.; Majeed, A.; Saxena, S.
Summary: Background: The role of early thiopurine treatment in inflammatory bowel disease (IBD) is unproven. Aim: To quantify the impact of timing and duration of thiopurines on the risk of first surgery in children and young people with IBD using a population‐based cohort. Methods: We constructed an incident cohort of children and young people aged <25 years, diagnosed with Crohn's disease (CD) or ulcerative colitis (UC) from 1990 to 2009. We used Cox proportional hazards modelling to determine the impact of early thiopurine use, commenced within a year of diagnosis on risk of first surgery. Results: We identified 1595 and 1175 incident cases of CD and UC respectively with a mean length of follow‐up of 4.3 years/person. There were 216 (13.5%) and 73 (6.2%) surgeries for CD and UC patients between 1990 and 2009 respectively. In CD among thiopurine users, the absolute risk of surgery at 5 years for early thiopurine use vs. late was 15.3% (95% CI: 10.5–22.1) vs. 22.1% (95% CI: 18.1–26.9) respectively. After adjustment, the early use of thiopurines was associated with a reduction in risk of first surgery of 39% (HR 0.61, 95% CI: 0.41–0.91) over the 20‐year study period. In UC, early thiopurine use offered no additional benefit. Conclusions: In Crohn's disease, early treatment with thiopurines in children and young people is associated with an appreciable reduction in the risk of surgery, but early treatment does not reduce surgical risk in UC.